THE NORMATIVE IRRELEVANCE OF AUSTIN’S COMMAND THEORY IN INTERNATIONAL LAW - Allan Munyao (Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractJohn Austin has been widely criticized and supported in equal measure for his bold assertion that international law is not ‘real law’ due to the lack of a ‘sovereign’. This article explores Austin’s position and analyzes it as against its veracity in relation to current legal systems; modern contemporary international law; and analysis of legal questions in the international arena. While indeed Austin’s position was true about the legal systems of his time, the same cannot be transposed into the international legal system. If on the other hand the transposition is necessary, it will be shown that international law is indeed ‘real law’ with a somewhat real ‘sovereign’ just like any municipal law